ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN MASALAH ALJABAR - Junaidah Wildani (Unisda Journal of Mathematics and Computer Science (UJMC), 2018)
This research aimed to analyse students’ error in solving algebra problem. With the research questions are: 1) Among four types of algebraic problem, in which problem students make error the most? 2) How is students’ error characteristics based on the type of algebraic problem? And 3) What type of error students make the most when solving algebraic problem?The subject of this research is 24 students from grade VIII A MTs Ma’arif Assa’adah 2 Sampurnan-Bungah-Gresik. Students were asked to solve algebra problems which consist of four problems. Each problem represents each type of algebra problem. Students’ work then analysed using Newman’s error analysis which classified error into five types; reading, comprehension, transformation, processing skill, and encoding. In this research the ‘reading’ category was left out. The result shows that among four types of algebra problem, students made error the most when solving the problem of algebra as the use of mathematical models to represent and understand quantitative relation. On the problem of algebra as representation and analysis of mathematical situation and structure using algebraic symbol, the most common error located in transformation. This error was also dominant in the problem of algebra as understanding pattern, relation, and function. As for algebra problems as the use of mathematical models to represent and understand quantitative relation, the dominant error located in comprehension. Having said that, transformation and comprehension is the type of error that happened the most.